Pemanfaatan Media Sosial Dalam Ekonomi Kreatif Untuk Menciptakan Ide Bisnis Bagi Para Wirausahawan Muda - Cecilia Azhara Ayuningtiyas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The era of society 5.0 is an era that applies the ease of technological innovation in the era of the industrial revolution 4.0 to facilitate activities, especially in the economic sector. This research aims to see the use of technology such as social media in the creative economy so as to create new businesses for young entrepreneurs. To support this statement, this study uses the literature review method in finding supporting data. Almost all internet users must have social media, especially among teenagers and young people, so that it makes business people especially among teenagers and young people make creative new innovations in building a business. This shows an increase in creative economy development that has great potential and will have a significant impact on the Indonesian economy.